The Effect of COVID-19, KUR and Communication on the Productivity of MSME Entrepreneurs Partners PT Perkebunan Nusantara III Medan City - Jenari Tamariska Br Sembiring; Fitri Febriani Sembiring; Yunika Sophia Br Surbakti; Deni Faisal Mirza (Publikasi Indonesia, 2022)
In the business world, it is very necessary to have a policy in dealing with all problems that come, even unexpected problems. Sensitivity to the situation is needed and contributes in dealing with ongoing problems for the common good and the company. This study aims to determine the effect of COVID-19 on KUR and Communication on Productivity of MSME Entrepreneurs Fostered Partners of PT. Nusantara III Plantation, Medan City. The research method used is a quantitative method of data processing in this study using casual associative. This research was carried out directly and the population of this study were MSME entrepreneurs of Fostered Partners with a sample of 50 entrepreneurs and then analyzed by distributing questionnaires to a number of samples. and the results of respondents' answers were processed using SPSS version 26.00 to obtain clear and accurate information. The results of this study partially and simultaneously COVID-19, Kur and Communication affect the productivity of MSME entrepreneurs assisted by PT. Perkebunan Nusantara III Medan City and the magnitude of the influence of the independent variable on the dependent variable is 34% seen from the determination test.